PREVALENCE OF MALNUTRITION AND RELATED FACTORS IN PEDIATRIC PATIENTS WITH BILIARY ATRESIA TREATED AT CHILDREN'S HOSPITAL 2 - Phạm, Thế Nhân Tài; Huỳnh, Ngọc Vân Anh; Lê, Thị Kha Nguyên; Nguyễn, Hoàng Thanh Uyên; Nguyễn, Hoàng Nhựt Hoa; Nguyễn, Thị Thu Hậu (Tạp chí Dinh dưỡng và Thực phẩm, 2024)
Aims: To determine the prevalence of malnutrition and related factors in children with biliary atresia being treated at Children's Hospital 2.Methods: A cross-sectional study was conducted on 120 children with biliary atresia being monitored and treated at the Hepatology Department of Children's Hospital 2 from March to April 2024.Results: The prevalence of malnutrition according to MUAC was 47.7%, stunting was 30.8%, wasting was 12.4%, and malnutrition based on BMI was 10%. Factors related to malnutrition according to MUAC include younger age groups and blood albumin levels. Stunting malnutrition was related to blood albumin levels. Wasting malnutrition was related to Kasai surgery, and younger age groups were related to malnutrition based on BMI. Supplementation with MCT was associated with stunting and BMI based-on malnutrition. Maltose supplementation was associated with all four types of malnutrition. Tube feeding was associated with wasting and BMI based-on malnutrition. Nutritional counseling was associated with stunting.Conclusion: The screening, assessment, and nutritional support for children biliary atresia have not received adequate attention. Regular monitoring of the nutritional status, using both overall anthropometric indices and specific anthropometric indices to early identify the risk of malnutrition in this group. It is important to enhance educational efforts to ensure caregivers recognize the crucial role of nutrition and nutritional counseling for children with biliary and cholestatic jaundice in general.